Peran Media Sosial dalam Pengawasan dan Pencegahan Korupsi di Indonesia - Jonathan Cahyadi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study examines the role of social media in monitoring and preventing corruption in Indonesia, an issue that has become a primary concern among the public and government. With the increasing number of social media users in the country, these platforms are expected to serve as effective tools in enhancing public participation in overseeing corrupt practices. The research explores various aspects, including how social media enables the community to report corruption cases, share information, and build collective awareness about the impact of corruption. Additionally, this study highlights the challenges faced in utilizing social media, such as unequal access, negative responses from authorities, and the phenomenon of information fragmentation that can hinder constructive dialogue among the public. Through a literature review approach, this research analyzes various relevant sources to provide in-depth insights into the impact and effectiveness of social media in preventing corruption. The findings of this study are expected to offer recommendations for maximizing the potential of social media as a tool to support transparency and public accountability in Indonesia. With a better understanding of the role of social media, it is hoped that both the public and government can collaborate more effectively in the fight against corruption, thereby creating a cleaner and more accountable environment for future generations.